Pelatihan Pembuatan Konten Digital untuk Mendukung Kegiatan Promosi pada UMKM Seblak di Kedung Waringin - Alviansyah Rizki Fatkhu; Etty Zuliawati Zed; Awaladina Suhaebah Siti; Dewi Winarty Mayly (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
MSMEs (Enterprises, Micro, Small and Medium Enterprises) play a crucial role in the economy in Indonesia, but many MSME owners (Micro, Small and Medium Enterprises) have not maximized digital technology in their business activities, so they cannot develop and explore technological advances. Seblak MSMEs in Kedung Waringin are one of the businesses that have great potential to compete and promote in digital technology. This community service activity aims to provide digital content creation training to Seblak MSME actors in Kedung Waringin. This training includes creating attractive product photos, creating simple promotional videos, as well as marketing techniques through social media such as Instagram and Tiktok. The methods used in the training include discussions, and content creation practices. The results of this activity showed an increase in participants' understanding of the importance of digital content in supporting promotions and abilities in creating relevant and interesting Seblak content in Kedung Waringin. With this training, it is hoped that MSMEs will carry out more effective digital promotions so that they can increase their competitiveness through this training. The number of participants is expected to be approximately 20 participants of Seblak MSMEs in Kedung Waringin so that they can create maximum results